The first woman in the republic : a cultural biography of Lydia Maria Child - Karcher, Carolyn L., 1945- (New Americanists., 1994)
"Taking its title from the accolade William Lloyd Garrison bestowed on Child - "she is the first woman in the republic"--This innovative cultural biography recreates the world as well as the life of a major nineteenth-century figure whose career encompassed issues central to American history. Carolyn L. Karcher captures the throes of a tumultuous era that saw the mass transfer of many Native tribes, ferocious mob violence against abolitionists and African American communities, bitter dissension among reformers over tactics and principles, a dramatic transformation in women's lives, a Civil War unprecedented not only for its carnage but also for its character as a liberation struggle, and a tragically aborted Reconstruction. She explores the key role Child played in shaping American culture at a formative moment in its development and reveals her impact on almost every facet of nineteenth-century letters. She also takes readers into the private life of a complex woman, riven by deep contradictions and remarkably honest about her feelings. This definitive biography restores to the public an eloquent writer and reformer who embodied the best of the American democratic heritage."--Provided by publisher.